This preview shows page 1. Sign up to view the full content.
Unformatted text preview: unit −− − − − −→
add 1 to each x-coordinate y = g2 (x) = −x2 y = g3 (x) = g2 (x − 1) = −x2 + 2x − 3 −2 horizontal stretch by a factor of 2 −− − − − − − − −→
multiply each x-coordinate by 2 y = g3 (x) = −x2 + 2x − 3 y = g (x) = g3 1
2x = − 1 x2 + x − 3
4 We have kept the viewing window the same in all of the graphs above. This had the undesirable
consequence of making the last graph look ‘incomplete’ in that we cannot see the original shape
of f (x) = x2 . Altering the viewing window results in a more complete graph of the transformed
function as seen below. y = g (x)
This example brings our ﬁrst chapter to a close. In the chapters which lie ahead, be on the lookout
for the concepts developed here to resurface as we study diﬀerent families of functions. 104 1.8.1 Relations and Functions Exercises 1. The complete graph of y = f (x) is given below. Use it to graph the following functions.
View Full Document